Effects of Angiotensin Converting Enzyme Inhibitors and Angiotensin Receptor Blockers in Contrast-Induced Nephropathy - Letian Zhou; Shaobin Duan (Kidney & Blood Pressure Research, 2014)
Contrast-induced nephropathy (CIN) is considered the third leading cause of iatrogenic acute kidney injury in high-risk patients undergoing radiographic procedures. The main mechanism leading to CIN is medullary hypoxia due to decreased renal blood flow, secondary to renal artery vasoconstriction and direct tubular toxicity by contrast medium. Furthermore, experimental data suggests that an activated renin-angiotensin-aldosterone system (RAAS) plays a role in the pathophysiology of CIN. However, the role of RAAS blockers, including angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) in CIN is controversial. They have been reported to be effective in the prevention of CIN in previous studies, but some studies have concluded that they were associated with an increased risk of CIN, especially in patients with pre-existing renal impairment. In summary, there is no solid data to link ACE inhibitors and ARB to CIN, and larger randomised controlled trials are necessary to further investigate their role in the development of CIN. In this review, we discuss the pathophysiology of CIN, the role of RAAS on the development of CIN, and the effect of RAAS blockers on CIN.